2012
DOI: 10.1103/physrevb.85.024114
|View full text |Cite
|
Sign up to set email alerts
|

Energy-based yield criterion for PMMA from large-scale molecular dynamics simulations

Abstract: We use molecular dynamics (MD)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 29 publications
2
49
0
Order By: Relevance
“…Despite these limitations, molecular simulations are playing an important role in the development of a fundamental understanding of physical and mechanical behavior of polymers and they have been shown to capture nontrivial trends such as the dependence of yield and post‐yield on temperature, thermal history, deformation rate and loading path, see, for example, Refs. and . In addition, physics‐based constitutive models can be used to map MD results to the scales of interest in applications; in many cases, this requires extrapolating MD results to the time and spatial scales of interest in the application and is a topic of ongoing research.…”
Section: Predictions Of Materials Propertiesmentioning
confidence: 99%
“…Despite these limitations, molecular simulations are playing an important role in the development of a fundamental understanding of physical and mechanical behavior of polymers and they have been shown to capture nontrivial trends such as the dependence of yield and post‐yield on temperature, thermal history, deformation rate and loading path, see, for example, Refs. and . In addition, physics‐based constitutive models can be used to map MD results to the scales of interest in applications; in many cases, this requires extrapolating MD results to the time and spatial scales of interest in the application and is a topic of ongoing research.…”
Section: Predictions Of Materials Propertiesmentioning
confidence: 99%
“…Recent MD studies have shown that the Dreiding force field can be successfully used for the predictions of the elastic properties of CNT composites, yield criterion for PMMA and the crystallization of polymer chains on the CNT walls, respectively [32,46,47]. Furthermore, the Dreiding force field parameters can be extended to include atomic bonds with a user specified stiffness and length.…”
Section: Force Fields and Potential Energymentioning
confidence: 97%
“…Computational MD methods offer the capability of systematically studying the influence of geometry, defects, and material parameters on the mechanical stability of nanostructures. In addition, it helps in predicting and understanding the mechanical behavior of materials on an atomistic level in experiments and applications better [32].…”
Section: Introductionmentioning
confidence: 99%
“…39 The equations of motion are solved using the rRESPA multi-timescale integrator to speed up the simulations 40 with a timestep of 4 fs. Our prior work on thermoset 41,42 and thermoplastic 43 polymers shows that Dreiding provides an accurate description of thermo-mechanical properties of these materials.…”
Section: Methodology a Computational Detailsmentioning
confidence: 99%